SIMILARITIES OF DEFENSE MECHANISM BETWEEN LILLY ON S.A SWANN’S WOLFBREED AND LUCY ON LYNN OKAMOTO’S ELFEN LIED - Adi Saputra, Bayu; Andayani, Ambar (TANDA, 2021)
This study discusses comparison of defense mechanism phenomena performed by Lilly in S.A Swann's Wolfbreed and Lucy in Lynn Okamoto's Elfen Lied. Purpose of this study is to answer two points: Defense mechanism performed by Lilly and Lucy, and similarities between defense mechanisms used by two characters. This study uses qualitative research because data is taken from quotations in stories. This study uses a psychoanalysis approach, defense mechanism to analyze data. Data sources for this study are novel Wolfbreed by S.A Swann and manga Elfen Lied Omnibus by Lynn Okamoto. This study found that Lilly and Lucy perform a defense mechanism due to tragic events they have experienced. It makes anxiety in their minds which triggers them to perform defense mechanisms. There are similarities between Lilly and Lucy's defense mechanisms. Authors, S.A Swan and Lynn Okamoto show main character's suffering because of differences between them and people around them.